A numerical analysis of friction stir welded joint using FEA. (2022) - Logesh, M.; Kumar, D.Vijaya; Shankaranarayana, Ramesh; Sathyamurthy, Ravishankar; Dhanapal, Balaji
Abstract: The present work deals with numerical analysis of welding by the FEM. Attempts have been made to determine temperature distribution, distortion, and residual stresses due to welding by finite element method in welded plate structures. General-purpose finite element software ANSYS was used. The FE analysis is split into two parts. To acquire the global temperature history generated during the welding process, a nonlinear transient thermal analysis is initially performed. The temperatures acquired from the thermal analysis are then used as loading to the stress mode in the stress analysis. Though the numerical model gives a more accurate result always there occurs a difference between the numerical result and the experimental result an error of 10.53% between the experimental and the simulated result was obtained.